2013
DOI: 10.1590/s0104-026x2013000200004
|View full text |Cite
|
Sign up to set email alerts
|

Feminismo, Iglesia Católica y derechos sexuales y reproductivos en el Chile post-dictatorial

Abstract: La sexualidad y la reproducción se han tornado en las últimas décadas campos de disputas entre sectores antagónicos, generando una dinámica regional de avances y regresiones en la agenda de derechos sexuales y reproductivos. Chile no ha sido la excepción, y muchas reformas en estas materias han sido frenadas por la oposición ejercida por los sectores más conservadores, mientras otras simplemente no han llegado siquiera a abrirse a discusión pública. La literatura suele destacar la existencia de dos grandes cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
0
6
0
7
Order By: Relevance
“…This positive association between increased education and support for abortion liberalisation is well documented in the literature (Cesar et al 1997;Alves Duarte et al 2002;Becker, Garcia, and Larsen 2002;Palermo et al 2010;Valencia Rodríguez et al 2011;Wilson et al 2011;Morán Faúndes 2013;Faúndes et al 2013;Jelen and Doc Bradley 2014) and may be due to increased exposure to ideas surrounding gender equity in higher education or to increased work opportunities for women, which both force and enable women and families to consider timing and limiting fertility. The relationship with income was not monotonic: women in the two middle income categories were consistently more supportive of abortion legalisation compared to those in the lowest and highest income categories.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This positive association between increased education and support for abortion liberalisation is well documented in the literature (Cesar et al 1997;Alves Duarte et al 2002;Becker, Garcia, and Larsen 2002;Palermo et al 2010;Valencia Rodríguez et al 2011;Wilson et al 2011;Morán Faúndes 2013;Faúndes et al 2013;Jelen and Doc Bradley 2014) and may be due to increased exposure to ideas surrounding gender equity in higher education or to increased work opportunities for women, which both force and enable women and families to consider timing and limiting fertility. The relationship with income was not monotonic: women in the two middle income categories were consistently more supportive of abortion legalisation compared to those in the lowest and highest income categories.…”
Section: Discussionmentioning
confidence: 74%
“…In the existing literature from Latin America, increased levels of education (Cesar et al 1997;Alves Duarte et al 2002;Becker, Garcia, and Larsen 2002;Palermo et al 2010;Valencia Rodríguez et al 2011;Wilson et al 2011;Morán Faúndes 2013;Faúndes et al 2013;Jelen and Doc Bradley 2014), increasing income or socioeconomic status (SES) (Alves Duarte et al 2002;Garcia et al 2004), paid employment (Duarte Osis et al 1994;Palermo et al 2010) and lack of religious affiliation and/or less frequent religious attendance (Gogna et al 2002;Lisker, Carnevale, and Villa 2006;Silva et al 2009;Palermo et al 2010;Wilson et al 2011;Faúndes et al 2013) are associated with increased support for a woman's right to access abortion. Overall, studies from Latin America indicate that increasing age is associated with increased support for abortion (Gogna et al 2002;Garcia et al 2004;Lisker, Carnevale, and Villa 2006;Faúndes et al 2013), though at least one study has found that individuals over the age of 60 are less supportive ) and another found no association (Jelen and Doc Bradley 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, data from Chile on sexual aggression victimization and perpetration, particularly among young adults, is limited. In Chile, the Catholic Church is a strong source of influence on social norms and public policy, in particular referring to sexuality (Lehrer et al, 2009; Morán Faúndes, 2013). For example, abortion is illegal under any circumstances, including incest or rape (Amnesty International, 2015), and divorce, which was not legalized until 2004, is opposed by the Catholic Church (Blofield, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Lehrer, E.L., Lehrer, V.L. & Krauss, 2009;Morán Faúndes, 2013a), Chile es un país que se ha caracterizado por un férreo control conservador de sus políticas públicas de sexualidad y reproducción, derivado principalmente desde la Iglesia Católica. Ejemplos de esto son la difícil aprobación de la píldora anticonceptiva de emergencia, que recién ocurrió el año 2010 (Morán Faúndes, 2013b), la ilegalidad del aborto en cualquier tipo de circunstancia, incluyendo la violación o la inviabilidad del feto (Amnistía Internacional, 2015) y la legalización del divorcio en el año 2004 (Blofield, 2006).…”
Section: Discussionunclassified